Leftover bandwidth-aware peer selection algorithm for inter-datacenter content distribution - Yong-feng HUANG; Yong-qiang DONG; Shan-feng ZHANG; Guo-xin WU (Tongxin xuebao)
Due to the fact that leftover bandwidth appears during non-overlapping time intervals, an approach of using such bandwidth to distribute delay tolerant data was proposed, and then a distributs and scalable leftover band-width-aware peer selection algorithm named LBAPS was designed. LBAPS avoids centralized optimization method that fails to effectively utilize leftover bandwidth when multiple destinations occur. In LBAPS, a node selection strategy based on synthetical evaluation was presented in order to find appropriate nodes h leftover bandwidth currently. In addition, two other strategies, i.e., resource reservation based on threshold and exiting upload upon the length of time slice, were put forward. With these two strategies, nodes with more leftover bandwidth get higher priority to obtain file blocks; be-sides, different file blocks can be delivered to different nodes as soon as possible. On the basis of LBAPS, a content cloud prototype, P2PStitcher was implemented. Experimental results on PlanetlLab show that the strategies proposed in LBAPS are effective to decrease the average delivery time.